Modification of the Double-Disk Test for Detection of Enterobacteriaceae Producing Extended-Spectrum and AmpC β-Lactamases - Pitout, J. D. D. (American Society for Microbiology, 2003)
Detection of extended-spectrum β-lactamases (ESBLs) in AmpC-producing Enterobacteriaceae is problematic. A modification of the double-disk test (MDDT) has been developed for successful detection of ESBLs in gram-negative bacilli producing well-characterized β-lactamases as well as 212 clinical isolates of Enterobacter cloacae, Enterobacter aerogenes, Serratia marcescens, and Citrobacter freundii. MDDT accurately differentiated between ESBL producers and derepressed chromosomal AmpC mutants. MDDT provides a cost-effective alternative approach for clinical microbiology laboratories for routine susceptibility testing with simultaneous detection of ESBLs in Enterobacteriaceae.